School Location, Class Size and Teaching Experience as Determinants of Academic Achievement of Students’ in Lagos State. - Abosede, Subuola Catherine (NIU Journal of Humanities, 2018)
This study examined school location, class size and teaching experience as determinants of academic achievements in Business Studies. This study adopted a survey research design of ex-post facto. Forty (40) Business studies teachers and four hundred (400) junior secondary school students (JS 3) formed the sample of the study. The sample were drawn from private and public secondary schools in Ikorodu Local Government Area of Lagos State, Nigeria. Two instruments were used for data collection. They are: (i) Questionnaire for Business Studies teachers’ demographic data has items such as school location, years of teaching experience, area of specialization, sex, age and so on. (ii) Business Studies Achievement test questionnaire. Data were analysed using Multiple Regression, Analysis Coefficient. In carrying out the study, three hypotheses were formulated and tested. The results obtained were tested for significance at 0.05 level of confidence. Findings revealed that school location, class size and teaching experience significantly predict students’ achievement in Business Studies. Class size was more potent predictor of academic achievement, followed by school location, while teaching experience was not a good predictor of academic achievement. There was also a significant relationship between the three predictor variables and academic achievement. Based on this, it was recommended among others, that critical efforts should be made by stakeholders to improve the school location and environment, while the class size should be made moderate and manageable.  Also, teachers’ professional experience should be considered in reward system so to encourage the teachers to be more productive and committed to the teaching profession.